Possibilities of Surgical Treatment of Pulmonary Embolism in Patients After Spinal Surgery - S. A. Fedorov; A. P. Medvedev; L. Ya. Kravets; L. M. Tselousova (Неотложная медицинская помощь)
Aim of study. Comprehensive assessment of clinical and hemodynamic results of surgical treatment of high- and intermediate-high risk of pulmonary embolism in a group of patients who underwent spinal surgery.Materials and methods. The analysis of the results of open surgical treatment of pulmonary embolism in high- and intermediate-high-risk patients after neurosurgical operations on the spine in the period from 2013 through 2019. The study group included 5 patients. The average age of patients was 59.74±3.42 years. The Wells index was 9.2±2.4. The Pesi index of the studied patients was in the range of 100–126, which allowed them to be classified as a high-risk group of 30-day mortality (class IV). Clinical manifestations of pulmonary embolism developed on average by 5.8±1.08 days after the initial neurosurgical intervention. The calculated pressure in the pulmonary artery was 56.6±8.22 mm Hg. In all cases, surgical intervention was performed for emergency indications, in conditions of artificial blood circulation, without aortic compression during the main stage of the operation.Results. The 30-day survival rate of patients was 100%. Among non-lethal postoperative complications, acute cardiovascular failure and hepatic-renal failure prevailed, which were levelled by the time the patients were transferred to a cardiac hospital. In 1 patient, the early postoperative period was complicated by the development of exudative pericarditis with cardiac tamponade, which required a finger revision of the anterior mediastinum, its drainage for 2 days. In all cases, there was an improvement in the condition of patients, in the form of increased tolerance to physical activity. The estimated pressure in the pulmonary artery at the time of discharge was 24.69±8.03 mm Hg.Conclusions. Surgical treatment of acute pulmonary embolism of high- and intermediate-high risk of early death in a group of patients with a neurosurgical profile is a highly effective and reliable method with great prospects for application.